Analysis of the current trends in digital transformation (Economics and region, 2023)
The article is devoted to the study of the directions of digital transformation at the current stage of economic development in order to identify the best ways to improve business models and gain competitive advantages in both the short and long term. The study includes an analysis of the categories of remote work participation and key areas and technologies of digital business transformation. The research findings highlight the importance of focusing on the categories of remote work for efficient use of working time and successful integration of modern elements into business models. The main areas of digital transformation include hyper-automation, hybrid workplace model, digital banking, 5G technologies, artificial intelligence (AI) and Web 3.0. The interaction between these areas determines the prospects for successful implementation of digital innovations. The study shows that companies that initiate changes in corporate culture and implement digital transformation at an early stage are more likely to move towards strategic development and achieve success.
Keywords: digital transformation; blockchain; hyper-automation; hybrid workplace; artificial intelligence; 5G technologies; Web 3.0; digital banking